Effects of hardness and grain size on wear resistance of polycrystalline cubic boron nitride. (February 2023) - Zhou, Li; Zhang, Jiawei; Li, Shuaiqi; Tian, Yi; Wang, Junpu; Huang, Mengyang; Yuan, Qin; Li, Xin; Kou, Zili; He, Duanwei; Zhan, Guodong
Abstract: Exploring the factors affecting the wear resistance of superhard materials is interesting and has practical industrial applications. Characterizing the hardness and grain size of superhard materials is more convenient and simple than measuring their wear resistance. Therefore, we expect to obtain a quantitative relationship between the hardness and grain size of superhard materials and their wear resistance. In this work, a series of polycrystalline cubic boron nitride (PcBN) compacts with different grain sizes and hardnesses were sintered under high temperature and pressure. Furthermore, turning tools were manufactured using these PcBN samples. The edge wear of the turning tool during the turning of granite was examined. Based on aforementioned measurements, the relationship between hardness and wear resistance is examined with same grain size (1–2 μm) and the influence of PcBN grain size on wear resistance is investigated under the same hardness (44.0 ± 1.2 GPa). The results show that the wear resistance of PcBN exhibits a regression parabolic and linearly increasing trends with the increase in hardness and grain size, respectively. Further investigation reveals that the compactness of PcBN materials, the bonding strength between the crystal grains, and the depth of the embedded crystal grains are critical factors affecting the wear resistance. These works can serve as a practical guide for the preparation as well as research and development (R&D) of PcBN and are expected to be extended to the R&D and application of other superhard materials and hard ceramics.